Inside outside : between architecture and landscape - Berrizbeitia, Anita; Pollak, Linda (Hi Marketing, 1999)
"Inside Outside constructs a framework of interpretation for architecture and landscape architecture in order to disclose relations between them which are normally overlooked. Five operations - reciprocity, materiality, threshold, insertion, and infrastructure - each initiate an alternative way of looking at the construction and representation of relationships between architecture, landscape, city, and individuals. Twenty-four projects each contribute in a unique way to the definition of an operation."--BOOK JACKET.